Gender norms and ideologies about adolescent sexuality: A mixed-method study of adolescents in communities, south-eastern, Nigeria - Agu, Ifunanya Clara; Mbachu, Chinyere Ojiugo; Ezenwaka, Uchenna; Eze, Irene; Ezumah, Nkoli; Onwujekwe, Obinna (Frontiers in Sociology, 2022)
Background: Sexual and reproductive health choices and behaviours of adolescents are shaped by gender norms and ideologies which are grounded in cultural beliefs. This study examined the perspectives of adolescents about the influence of gender norms and ideologies on sexuality. Methods: A cross-sectional study was undertaken in three urban and three rural communities in south-eastern Nigeria using quantitative and qualitative research methods. A modified cluster sampling procedure was used to select respondents. Data were collected from 1057 adolescents and twelve focus group discussions with unmarried adolescents aged 13 to 18 years. For the quantitative data, univariate, bivariate and probit regression analyses were performed using Stata while the thematic framework approach was used to analyze qualitative data. Results: The dominant beliefs among adolescents are that: it is wrong for unmarried adolescents to have sex (86.4%); unmarried adolescents should abstain from sex (89.3%); consent should be obtained before sexual intercourse (89.1%); it is a girl’s responsibility to ensure she does not get pregnant (66.5%), and sex should be initiated by boys (69.6%). Gender (boy or girl) was a predictor of belief in premarital abstinence (t-value = -3.88), belief that premarital sexual intercourse is acceptable provided contraceptive is used (t-value =3.49, CI 1.14–0.49), belief that premarital sexual intercourse is wrong (t-value =-2.24) and, belief that sex should be initiated by boys only (t-value =-4.37). Adolescent boys were less likely to believe in pre-marital abstinence and less likely to believe that pre-marital sex among adolescents is wrong compared to girls. They were also more likely to believe adolescents can have sex provided contraceptive is used compared to girls. Qualitative findings revealed adolescents’ beliefs that girls feel shy initiating sex and that boys experience more urge for sex hence, boys were perceived to be responsible for initiating sex. Both boys and girls experience pressure to have sex however, boys were described to experience more pressure from peers to have sex. Peer-to-peer communication, quest for material possessions and low socioeconomic conditions contribute to peer pressure to engage in sex. Conclusion: Adolescents’ beliefs about sexuality underline the need to contextualize interventions to address these norms and ideologies.